Molecular-based design and emerging applications of nanoporous carbon spheres - Liu, Jian; Wickramaratne, N.; Qiao, S.; Jaroniec, M. (Nature Publishing Group, 2015)
Over the past decade, considerable progress has been made in the synthesis and applications of nanoporous carbon spheres ranging in size from nanometres to micrometres. This Review presents the primary techniques for preparing nanoporous carbon spheres and the seminal research that has inspired their development, presented potential applications and uncovered future challenges. First we provide an overview of the synthesis techniques, including the Stöber method and those based on templating, self-assembly, emulsion and hydrothermal carbonization, with special emphasis on the design and functionalization of nanoporous carbon spheres at the molecular level. Next, we cover the key applications of these spheres, including adsorption, catalysis, separation, energy storage and biomedicine-all of which might benefit from the regular geometry, good liquidity, tunable porosity and controllable particle-size distribution offered by nanoporous carbon spheres. Finally, we present the current challenges and opportunities in the development and commercial applications of nanoporous carbon spheres.